Effect of cutting and regrowth on yield, crude protein and digestibility of Maralfalfa (Pennisetum purpureum x Pennisetum glsucum ) in two seasons in Pucallpa, Peru - Del Aguila L., Roberto (2023)
The purpose of this study was to evaluate the yield of dry matter (DM), crude protein (CP) and in vitro digestibility of dry matter (IVDMD) at four cutting heights and five maturity times of Pennisetum sp (Maralfalfa) during the periods of greatest and least precipitation in Pucallpa, Peru. Cuts were made at 0, 10, 20 and 30 cm height from the ground at 28, 35, 42, 49 and 56 days of regrowth. Plant height, number of stems, number, length and width of leaves, DM, CP and IVDMD yield were evaluated under a complete randomized design with a 4x5 factorial arrangement and 4 repetitions. The plant reached 120.5 cm in height at 56 days of regrowth. At the beginning of the growth period, it had 28 stems and 127 leaves, decreasing until it was established on 15 stems and 58 leaves after 56 days. In that same period the leaves grow up to 77.9 cm long and 2.3 cm wide. The DM performance increases when the cutting height is higher. The DM (kg/ha/cut) in the wet season (391.8 ± 386.1) was higher (p<0.05) than in the dry (235.5 ± 205.1). Plants cut at 30 cm height achieved the highest forage yields (DM kg/ha/cut) at 49 days (557.8 ± 322.8) and 56 days (537.5 ± 138.5) (p<0.05). The DM content of the plant was 15.9%. The highest CP content (13%) was obtained in 30 cm high cuts with 28 days of growth. The average PC was 9.645 ± 1.63 in the season of lowest precipitation and 11.94 ± 1.94 in the season of highest precipitation. The IVDMD value at 0 cm height at 28 days (59.5 ± 19.4%) was similar to that at the cuts at 35 days (59.5 ± 5.5%). It is concluded that maralfalfa can produce up to 557.8 ± 322.8 MS kg/ha/cut, and reach 11.0% CP, while the IVDMD reaches 59.5%, and it can be considered as an option to improve the diet of animals in the humid tropics of Pucallpa.